Friendly fungi: symbiosis with commensal Candida albicans. Issue 9 (September 2022) - Shao, Tzu-Yu; Haslam, David B.; Bennett, Richard J.; Way, Sing Sing
Abstract : Mucosal tissues are constitutively colonized by a wide assortment of host-adapted microbes. This includes the polymorphic fungus Candida albicans which is a primary target of human adaptive responses. Immunogenicity is replicated after intestinal colonization in preclinical models with a surprising array of protective benefits for most hosts, but harmful consequences for a few. The interaction between fungus and host is complex, and traditionally, the masking of antigenic fungal ligands has been viewed as a tactic for fungal immune evasion during invasive infection. However, we propose that dynamic expression of cell wall moieties, host cell lysins, and other antigenic C. albicans determinants is necessary during the more ubiquitous context of intestinal colonization to prime immunogenicity and optimize mammalian host symbiosis. Significance: Fungi including Candida albicans colonize the human intestine with local and systemic host benefits, which require fungal immunogenicity in the commensal state. Investigating the molecular and cellular mechanisms sustaining this immunological symbiosis can generate approaches to therapeutically fine-tune immunity, optimize host protection, yet limit invasion. Highlights: Fungi that colonize the intestine convey unique symbiotic host benefits including tonic calibration of systemic immunity, and protection against invasive infection in rodents with potentially direct translational relevance to human immunity. Candida albicans colonization in mice protects against infection by antigenically unrelated pathogens, aberrant intestinal inflammation and injury, and can promote social behavior changes through systemic immunological influence. Immunogenicity during commensal colonization is beneficial to mice and occurs with dynamically regulated exposure of antigenic fungal cell wall ligands. Commensal C. albicans in mice are mucosa associated and can protect against intestinal injury induced by other commensal fungal species that primarily reside in the intestinal lumen. Commensal C. albicans are heterogeneous in humans and mice, with variations in immune-cell-damaging capacity associated with filamentation and production of the toxin candidalysin.